1997
DOI: 10.1002/(sici)1099-0739(199710/11)11:10/11<859::aid-aoc652>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic compounds in terrestrial organisms. III: Arsenic compounds inFormica from an old arsenic smelter site

Abstract: Total arsenic concentrations in the freeze‐dried pulverized ants (Formica sp.) and material from an ant‐hill collected at a former arsenic roasting facility were determined by inductively coupled plasma mass spectrometry (ICP–MS) after microwave digestion with nitric acid and hydrogen peroxide. The ants contained 12.6±0.9 mg As/kg dry mass, the ant‐hill material 5420±90 mg As/kg dry mass. Total arsenic concentrations in needles of Picea abies and Larix decidua (spruce and larch needles) were also determined, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Soil, food, and water contain predominantly inorganic arsenic: arsenite [As(OH) 3 , As(III)] and arsenate [H 2 AsO 4 -, As(V)] (Mandal and Suzuki 2002). Methylated arsenicals, specifically, monomethylarsonic acid [MMA(V)] and dimethylarsinic acid [DMA(V)], are also present as arsenic species in plants and invertebrates but in small amounts (Abedin et al 2002;Kuehnelt et al 1997;Moriarty et al 2009;Reimer et al 2010;Schaeffer et al 2006). Laboratory studies show that mammals methylate inorganic arsenic in vivo, and methylated compounds account for a significant portion of excreted arsenic in terrestrial animals (Styblo et al 2000).…”
mentioning
confidence: 99%
“…Soil, food, and water contain predominantly inorganic arsenic: arsenite [As(OH) 3 , As(III)] and arsenate [H 2 AsO 4 -, As(V)] (Mandal and Suzuki 2002). Methylated arsenicals, specifically, monomethylarsonic acid [MMA(V)] and dimethylarsinic acid [DMA(V)], are also present as arsenic species in plants and invertebrates but in small amounts (Abedin et al 2002;Kuehnelt et al 1997;Moriarty et al 2009;Reimer et al 2010;Schaeffer et al 2006). Laboratory studies show that mammals methylate inorganic arsenic in vivo, and methylated compounds account for a significant portion of excreted arsenic in terrestrial animals (Styblo et al 2000).…”
mentioning
confidence: 99%
“…Marine samples have so far provided the greatest number of naturally occurring arsenic compounds with up to 50 compounds identified (Nischwitz and Pergantis, 2006), although recent work revealed that terrestrial organisms also contain many of these compounds (Geiszinger et al 1998;Kuehnelt et al 1997;Watts et al 2008;Button et al 2009). There are clear patterns of arsenic compounds among marine organisms (Francesconi & Edmonds, 1997).…”
Section: Introductionmentioning
confidence: 83%
“…Significant amounts of arsenobetaine were also found in some mushroom species (Byrne et al 1995, Kuehnelt et al 1997a, and minor amounts in ants (Formica sp.) (Kuehnelt et al 1997c) and in earthworms (Geiszinger et al 1998). This might support the assumption that the terrestrial arsenic cycle resembles that of the marine cycle.…”
Section: Terrestrial and Marine Flora And Faunamentioning
confidence: 99%